Corrosion of Steel Reinforcements in Fly Ash- and Kaolin-based Geopolymer Concrete Immersed in Distilled Water and ASTM Seawater - Astutiningsih, S.; Rustandi, A.; Noermalasari, D. (Civil Engineering Dimension, 2013)
Corrosion behavior of steel bar in fly ash- and kaolin-based geopolymer concrete immersed in aggressive media of distilled water and ASTM seawater was compared to Portland cement concrete having similar mix design. An accelerated corrosion by applying 3 V potential on the steel bar was performed to obtain reasonable test results in a relatively short time. The potential and pH of the immersing media were measured from day 1 to day 10 and then plotted on Pourbaix diagram to predict passivation or corrosion state. At day 10, steel bar in Portland cement concrete were in corroded state both in distilled water and seawater. The best corrosion performance was for kaolin- based geopolymer concrete in which at day-10 the steel bar was passivated in both media. Steel bar in fly ash- based geopolymer concrete was passivated in distilled water but corroded in seawater.